Migrantes haitianos no Brasil (2010-2017): tensões e fronteiras - Cividini, Fátima Regina (2018)
Since 1500, Brazil has been formed by several migratory waves. In 2010, an earthquake in Haiti's capital city, Port-au-Prince, shook deeply both physical and governmental structures, placing most of its nationals at the poverty line. The difficulty of coming across employment and the proximity to Brazilians who were in Haiti through the UN Peacekeeping Troops (MINUSTAH) provided them with a vision of a prosperous, welcoming Brazil with employment opportunities. The arrival of Haitians to Brazil was widely publicized and reported by the media, narrating fragments of the identity from the Haitian immigrant, constructing and transforming concepts with regards to Haiti and the Haitians in the conscience of the Brazilian inhabitants. Such project aims to bring narratives with regards to Haitians, through electronic journals and interviews with Foz do Iguaçu organs which act directly onto Haitian immigration. In the introduction, the theoretical-methodological aspects of the research are presented. In its first chapter, a mapping regarding the news published in periodicals categorized by themes which emerged according to the study is carried out. In its second chapter, narratives are shown through interviews with Sister Terezinha Mezzalira from Casa do Migrante and Anderson Vargas de Lima from NUMIG - Federal Police, dealing with the process of entry and insertion of the Haitian in the region of Foz do Iguaçu-PR. In its third chapter, a discussion regarding the image of the Haitian which is passed through the narratives and what interferences such displacement brings to the Haitian is thus brought.